Steam turbine controllers design based on soft-computing techniques - Alawaad, Nasir Ahmed (Institute of Advanced Engineering and Science, 2020)
Steam turbine is viewed as a standout among hotspots for control age in the most recent decades, its elements examination end up being dynamically more basic. For this investigation, the model chose is of turbine speed control framework. The purpose behind this is that model is regularly experienced in refineries in a type of steam turbine that utilization hydraulic governor to control the speed of the turbine. To suit plan prerequisites, a mathematical model for the turbine was determined in light of transfer function and state space definition. There are two sorts of controllers for steam turbines which are traditional and modern controllers. Internal mode control with proportional integral derivative (IMC-PID) and linear quadratic controller (LQR) are classical type. Fuzzy logic controller (FLC) and intelligent optimization techniques like, ant colony algorithm (ACOA) and genetic algorithm (GA) are modern type. The proposed work centers on classical verses modern controllers. Results got demonstrate that embracing such a controller (GA) improves the design requirements and transient stability. The system control was actualized in simulation utilizing MATLAB/Simulink.